Comprehensive Identification and Characterization of Long Non-coding RNAs Associated With Rice Black-Streaked Dwarf Virus Infection in Laodelphax striatellus (Fallén) Midgut - Zhang, Jian-Hua; Dong, Yan; Wu, Wei; Yi, Dian-Shan; Wang, Man; Wang, Hai-Tao; Xu, Qiu-Fang (Frontiers in Physiology, 2020)
Long non-coding RNAs (lncRNAs) are involved in a variety of biological functions through transcriptional and post-transcriptional regulation. However, little is known about their functions in the process of insect mediated virus transmission. In the present study, we analyzed using RNA-Seq, the lncRNAs that were differentially expressed in response to Rice black-streaked dwarf virus (RBSDV) infection in Laodelphax striatellus (Fallén) midgut. A total of 13,927 lncRNAs were identified and over 69% were assigned to intergenic regions. Among them, 176 lncRNAs were differentially expressed and predicted to target 168 trans-regulatory genes. Ten differentially expressed lncRNAs were selected and their expression changes were validated by RT-qPCR. KEGG analysis showed that these target genes were enriched in the essential biological process, such as Purine metabolism, Valine, leucine and isoleucine degradation, and Fatty acid elongation. The expression levels of the differentially expressed lncRNAs and the predicted target genes that were significantly enriched in the Human papillomavirus infection pathway were analyzed by RT-qPCR. The results showed that several lncRNAs were co-expressed with their target genes. One of the lncRNAs called MSTRG15394 and its target gene, encoding a secreted protease inhibitor (PI), were up-regulated at the transcriptional level after RBSDV infection. Knockdown of MSTRG15394 could down-regulate the PI expression at mRNA level. Inhibition of either MSTRG15394 or PI expression by RNA interference promoted RBSDV accumulation in L. striatellus midgut. Our finding provides new insights into the function of lncRNAs in regulating virus infection in an important insect vector.